Influence of Horizontal Coopetition in Outbound Logistics on the Profitability of Micro and Small Enterprises: A Case of Arusha Handicraft Industry - Mnzava, Twazihirwa Tunzo; Raphael, Gwahula; Uiso, Hawa (PAN-AFRICAN JOURNAL OF BUSINESS MANAGEMENT, 2023)
This study assessed the influence of horizontal coopetition in outbound logistics on the profitability of micro and small enterprises in the handicraft industry using the Theory of Coopetition and Resource Dependence Theory as theoretical frameworks. The horizontal coopetition in outbound logistics is hypothesized to influence profitability, and the resource interdependence between the MSEs was thought to moderate the influence. A sample of 159 MSEs from a population of 297 MSEs in Arusha, Tanzania took part in the study, using a stratified random sampling method. A survey approach was used to collect the data, which were quantitatively analysed using the moderated multiple linear regression (MLR) model to test the hypotheses. The results before and after moderation revealed that horizontal coopetition in outbound logistics had a positive and significant influence on the profitability of the MSE. After the introduction of the moderator, the resource interdependence had no statistically significant moderation influence in the way horizontal coopetition in outbound logistics influenced the MSE profitability. The study had contextual limitations of generalization even in MSEs engaged in the handicraft industry. More research needs to be done in a rural setting, involving more variables of horizontal coopetition in outbound logistics, and factoring in the MSE attributes as moderators. It is recommended that similar studies be conducted in more tourist areas. More empirical data on horizontal coopetition from industry-specific MSEs are recommended to vindicate what was generated in this study since it would add more understanding and knowledge to the theory of coopetition.